Teletrabalho no serviço público: estudo de caso em um campus do Instituto Federal de Educação de São Paulo - Brizante, José Nilton Fuzaro (2021)
This work aims to deepen the theme of telework in public servisse brazilian, observing the potentials and gaps, aiming to analyze and describe the possible benefits for the institution, for the servers and for society as a whole, also highlighting the possible challenges and difficulties from the planning process to the implementation process and control. By conducting an exploratory research on the experience of the study on the possibility of implementing telework on a campus of the Federal Institute of Education of São Paulo, from 2019 to 2020, together with the literature review on the subject, mainly in recent scientific articles, qualitative interviews were carried out with those involved in the process, aiming to form the triangulation of data (research, observation and interview). In summary, it was possible to observe that the existence of a previous technical study contributed to the use of telework on that campus during the pandemic caused by Covid-19, even if in an emergency manner. It was also noted that even with some challenges and limitations, positive perceptions are superior compared to negative perceptions regarding the permanence and use of telework in the post-pandemic period.